Effects of Sugar Cane Expansion in Southeastern Mato Grosso do Sul and Possible Pathways Towards a Sustainable Agenda - Chiaravalloti, Rafael Morais; Santana, Silvia; Morais, Maria Silvia; Rocha, Luciani Maria Vieira; Freitas, Daniel Morais (Sustainability in Debate, 2014)
The Brazilian Alcohol program (Pró-Álcool) is pointed out as a sustainable development tool. However, the negative impacts produced throughout its production can minimize its benefits. In recent years, the area under sugar cane increased from 105 thousands hectares to more than 700 thousands hectares in the state of Mato Grosso do Sul. Nonetheless, little is known about the impacts faced by this region of Brazil. The goal of this project was to evaluate the sugarcane impacts in the Southwestern region of that state, through interviews, reports analysis and in loco visits. The better protection of Areas Legally Protected and the incensement in the number of enterprises formally registered are within the positive effects. Related to the negative impacts, stands out conflicts related to Indigenous Lands and issues related to the public health system in the cities analysed. The results point out the need, for the public governments create and coordinate actions, alongside other sectors, with clear statements focused on the sustainable development.